2020
DOI: 10.1016/j.aucc.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The experiences and needs of relatives of intensive care unit patients during the transition from the intensive care unit to a general ward: A qualitative study

Abstract: a b s t r a c tBackground: Relatives of intensive care unit (ICU) patients play an important role as caregivers and can experience emotional distress, also referred to as post-intensive care syndrome-family. A deeper understanding of what relatives go through and what they need may provide input on how to strengthen family-centred care and, in the end, contribute to the reduction of symptoms of post-intensive care syndrome-family. Method: This is a qualitative descriptive study with semistructured face-to-face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 29 publications
6
41
0
2
Order By: Relevance
“…The ambiguity between the positive and negative experiences during the transfer from the ICU to the general wards is in line with the studies of Cullinane and Plowright [ 24 ] and Cypress [ 25 ]. Snow et al [ 12 ] and Op ‘t Hoog et al [ 26 ] reported that the patients and their families were confused and felt abandoned because of conflicting advice from health care providers and an inability to communicate with the health care team for guidance. Forsberg et al [ 27 ] indicated feelings of anxiety, and fear on the part of the patient and the family during the transition to an unfamiliar environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambiguity between the positive and negative experiences during the transfer from the ICU to the general wards is in line with the studies of Cullinane and Plowright [ 24 ] and Cypress [ 25 ]. Snow et al [ 12 ] and Op ‘t Hoog et al [ 26 ] reported that the patients and their families were confused and felt abandoned because of conflicting advice from health care providers and an inability to communicate with the health care team for guidance. Forsberg et al [ 27 ] indicated feelings of anxiety, and fear on the part of the patient and the family during the transition to an unfamiliar environment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients need to be psychologically prepared to gradually separate from equipment and monitoring [ 13 , 30 ]. According to Op ‘t Hoog et al [ 26 ], this difference is less prominent depending on the contrast between the two wards, perhaps, some participants were better at putting the new context into perspective, or they had a different coping style. Patients experienced the shift from being the center of all attention to being just ‘one in the crowd’.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios de intervención que utilizan diarios de la UCI o estrategias de comunicación personalizadas han demostrado ser prometedores para disminuir la carga de los síntomas del TEPT (50). Así, el personal de enfermería puede desempeñar un papel fundamental en la satisfacción de las necesidades de la atención centrada en la familia, especialmente durante las diversas transiciones y transferencias que realizan los pacientes de la UCI (52).…”
Section: Síndrome Post Unidad Cuidado Intensivo En La Familia Pics-funclassified
“…Unfortunately, this was not an isolated case. 5,6 This is a typical example. One morning one specialist changed my brother's medication regime without consulting the team.…”
Section: Clinical Case Reportmentioning
confidence: 99%